(Mis)Taken Identities: Reclaiming Identities of the "Collective Black" in Mathematics Education Research Through an Exercise in Black Specificity. Issue 1 (March 2017) - Gholson, Maisie L.; Wilkes, Charles E.
This chapter reviews two strands of identity-based research in mathematics education related to Black children, exemplified by Martin (2000) and Nasir (2002). Identity-based research in mathematics education is a burgeoning field that is disrupting narratives around the meanings of mathematical competence and brilliance. We argue that the identities of Black children as doers and knowers of mathematics are often confused (or mistaken) with stereotypical images of various social identities, as well as wrongly confiscated (or mis-taken), in order to perpetuate persistent narratives of inferiority, criminality, and general ineducability of these children. We use Black children as a particular example within the mathematics education research literature and argue that children within a so-called "collective Black" are subject to the same racial scripts that organize mathematics teaching and learning. While we acknowledge that important lines of identity-based research have emerged to reclaim the rightful identities of Black children and those within the collective Black, we conclude with a critique of this recent literature in which we note the troubling exclusion of girls and young children.